Criminalisation of Narcotics: A Critical Review of the Effectiveness of Criminalisation Policy and Alternative Responses in the Context of Modern Criminal Law - Hotland Thomas; Muklis Al’anam; M. Musa; Abd Thalib; Thamrin S (International Conference On Law And Social Sciences, 2024)
The policy of criminalisation of drugs has been the focus of public policy discussions and legal reforms in various countries. In the context of modern criminal law, this policy raises debates about its effectiveness in addressing the problem of drug abuse. Critique of drug criminalisation policies and alternative, more effective treatments. There is a need to evaluate the impact of criminalisation on the criminal justice system, public health, and human rights. In addition, we also explored alternative approaches such as decriminalisation, legalisation by regulation, and health-based approaches. Our findings suggest that alternative approaches may provide a more humane and effective solution to the drug problem. As such, this research is a normative study, with a conceptual, statutory, and comparative approach. The research therefore emphasises the importance of wider and further policy dialogue to understand the long-term implications of alternative strategies in diverse global contexts. It has a role to investigate and evaluate the effectiveness of drug criminalisation policies, as well as consider other policy alternatives in the context of modern criminal law. In other words, to deepen the understanding of whether drug criminalisation policies are effective in achieving their objectives, as well as exploring other options that may be better in the context of modern criminal law.